Visual pedagogy‐guided toothbrushing training to enhance fine motor skills in individuals with intellectual disabilities and impaired fine motor skills. (6th April 2021) - Tangnuntachai, Nichruethai; Smutkeeree, Apiwan; Jirarattanasopha, Varangkanar; Leelataweewud, Pattarawadee
Abstract: Aims: To evaluate the effect of visual pedagogy‐guided toothbrushing training on oral hygiene, toothbrushing ability, and fine motor skills in individuals with intellectual disability (ID) and impaired fine motor skills. Methods: This quasi‐experimental study comprised 37 subjects aged 6–24 years. The plaque index (PI), gingival index (GI), toothbrushing ability, and fine motor skills were evaluated before and after 3 and 6 months of individual visual pedagogy‐guided toothbrushing training. Friedman's post hoc test and Spearman's correlation coefficient were used for statistical analyses. Results: The PI, GI, toothbrushing ability, and fine motor skills of the 23 subjects who remained in the study at the 6‐month follow‐up period significantly improved from those measured at baseline ( p  < 0.05). A significant association was observed between the improvements in both toothbrushing ability and fine motor skills ( p  < 0.05). Conclusions: Visual pedagogy‐guided toothbrushing training could improve the oral hygiene and toothbrushing ability of individuals with ID and impaired fine motor skills. Moreover, improvements in the toothbrushing ability could enhance the fine motor skills of these individuals.